Darkness, Depression, and Descent in Anglo-Saxon England - Wehlau, Ruth (Richard Rawlinson Center Series for Anglo-Saxon Studies., 2019)
This collection of essays examines the motifs of darkness, depression, and descent in both literal and figurative manifestations within a variety of Anglo-Saxon texts, including the Old English Consolation of Philosophy, Beowulf, Guthlac, The Junius Manuscript, The Wonders of the East, and The Battle of Maldon. Essays deal with such topics as cosmic emptiness, descent into the grave, and recurrent grief. In their analyses, the essays reveal the breadth of this imagery in Anglo-Saxon literature as it is used to describe thought and emotion, as well as the limits to knowledge and perception. The volume investigates the intersection between the burgeoning interest in trauma studies and darkness and the representation of the mind or of emotional experience within Anglo-Saxon literature.